Knowledge and perceptions of type 2 diabetes among Ghanaian migrants in three European countries and Ghanaians in rural and urban Ghana: The RODAM qualitative study. - Ama de-Graft Aikins (PLoS ONE, 2019)
African migrants in Europe and continental Africans are disproportionately affected by type 2 diabetes (T2D). Both groups develop T2D at a younger age, and have higher morbidity and mortality from T2D and complications, compared to European populations. To reduce risk, and avoidable disability and premature deaths, culturally congruent and context specific interventions are required. This study aimed to: (a) assess perceptions and knowledge of T2D among Ghanaian migrants in Europe and their compatriots in Ghana and (b) identify specific perceptions and knowledge gaps that might predispose migrants to higher risk of diabetes. Data was gathered through 26 focus groups with 180 individuals, aged 21 to 70, from Amsterdam, Berlin and London and rural and urban Ashanti Region, Ghana. Thematic analysis of the data was informed by Social Representations Theory, which focuses on the sources, content and functions of social knowledge. Three key insights emerged from analysis. First, there was general awareness, across migrant and non-migrant groups, of T2D as a serious chronic condition with life threatening complications, and some knowledge of biomedical strategies to prevent diabetes (e.g healthy eating) and diabetes complications (e.g medication adherence). However, knowledge of T2D prevention and reduction of diabetes complications was not comprehensive. Secondly, knowledge of biomedical diabetes theories and interventions co-existed with theories about psychosocial and supernatural causes of diabetes and the efficacy of herbal and faith-based treatment of diabetes. Finally, migrants' knowledge was informed by both Ghanaian and European systems of T2D knowledge suggesting enculturation dynamics. We discuss the development of culturally congruent and context-specific T2D interventions for the research communities.